PEDAGOGICAL AND PSYCHOLOGICAL ASPECTS OF IMPROVING THE MECHANISMS OF DEVELOPING PROFESSIONAL PEDAGOGICAL CULTURE FOR STUDENTS OF PHYSICAL CULTURAL EDUCATION - B. B. Karimov (American Journals, 2025)
The article discusses the pedagogical and psychological aspects of improving the mechanisms of developing professional pedagogical culture for students in the educational direction of physical education and physical culture.
Keywords: Professional pedagogical culture, pedagogical ethics, communicative culture, educational approaches, reflective pedagogy.